The Politicization of the Supreme Court Justices : Has the content of the nomination hearings changed? - Färm, Elisa (My University, 2024)
The research topic of this thesis is the nomination process of the Justices for the Supreme Court of the United States. The political orientation of Supreme Court Justices has been contemplated by the public, so in this thesis I investigate whether such a shift towards a more political direction is evident in the research material. As the primary source for my work, I use the transcripts of the confirmed Supreme Court Justices’ confirmation hearings, starting from 1971. The focus will be on the questions from the members of the Senate Committee on the Judiciary posed to each justice nominee. The Committee consist of 21 senators from both political parties. The research question is if and how the content of the hearings has changed since the 1970s. The goal is to analyze the transcripts using discourse analysis, to determine if there has been a shift in the content of the hearings and if the use of the hearings for political purposes has been more prevalent at certain times. The key findings are that there were a few different kinds of changes throughout the timespan of the research, varying from inevitable reasons to other reasons, which were more affected by party politics. Inevitable reasons included, for instance, changes in the composition of the Committee of the Judiciary between the hearings. Other reasons included political and ideological factors, such as the nominee’s leaning towards a more liberal or conservative legal philosophy, which affected some senators’ attitudes. Changes in the language and rhetoric can be observed to shift towards more formal and less polite over time. The most significant change was observed in 2017 and after, following the rejection of the nomination process of President Obama’s last nominee Judge Garland. With this research, it cannot be concluded that the observed changes in the hearings directly contributed to the justices’ becoming more politically aligned. However, it does not exclude the possibility that other elements have influenced the justices, and it is possible that their objectivity has wavered over time. Further research on the topic would be beneficial, as the topic of the possible politization of a judicial branch remains relevant.
Keywords: The United States, Supreme Court, Discourse analysis, The United States Senate, Supreme Court Justices, Committee on the Judiciary.